Bioaccumulation of Polycyclic Aromatic Hydrocarbons and Mercury in Oysters (Crassostrea rhizophorae) from Two Brazilian Estuarine Zones. (31st July 2012) - Torres, Ronaldo J.; Cesar, Augusto; Pereira, Camilo D. S.; Choueri, Rodrigo B.; Abessa, Denis M. S.; do Nascimento, Marcos R. L.; Fadini, Pedro S.; Mozeto, Antonio A.
Abstract : Nowadays, organisms are increasingly being used in biomonitoring to assess bioavailability and bioaccumulation of contaminants. This approach can use both native and transplanted organisms in order to accomplish this task. In Brazil, most of the studies related to bioaccumulation of contaminants in oysters deal with metals. The present work employs this kind of test in Brazilian coastal estuaries (Santos and Paranaguá) to evaluate total mercury and polycyclic aromatic hydrocarbon contamination in sediments and oysters (native and caged Crassostrea rhizophorae ). The methodologies employed were based on known USEPA methods. Results have shown a significant contamination in Santos sediments and consequent bioavailability of organisms. Paranaguá sediments presented lower contamination in sediments, but native oysters were able to accumulate total Hg. The experiments done with caged oysters did not show significant bioaccumulation of Hg and PAHs in the Paranaguá site, but proved to be an excellent tool to assess bioavailability in the Santos estuary since they were able to bioaccumulate up to 1, 600% of total PAH in the samples from the inner part of this estuary when compared to control organisms. Multivariate statistical analyses employed to these results have separated the sites evaluated and the most contaminated samples from the least contaminated.